Preharvest factors and the heat sensitivity of field-grown ripening papaya fruit - Paull, R.E.
Mesocarp softening during papaya (Curicu papaya L.)ripening was impaired by heating so that areas of the flesh failed to soften. Disruption of the softening process varied with harvest date. The sensitivity of fruit to the injurious treatment was greatest during the winter months. During January, exposure to more than 27 min at 49°C was sufficient to induce areas in the mesocarp that failed to soften, whereas up to 45 min was required during April, July, August and September. Stepwise regression indicated that fruit with low mesocarp calcium were less sensitive to heat treatments. Preharvest weather in the day before and the mean of four days before harvest were not significantly correlated with fruit sensitivity. However, the mean of the rainfall, evaporation, minimum and maximum temperature in the three days before harvest were significantly correlated to fruit heat sensitivity. The three day mean of the minimum temperature had the greatest relationship to fruit heat sensitivity. When the three day mean minimum temperature was higher than 22.4"C, fruit injury did not occur.
Keywords: CARICAPAPQA; PAPAYA; HEAT STRESS; SOFTENING; ENVIRONMENTAL FACTORS AND RIPENING